Lessons from lymphatic filariasis elimination and the challenges of post-elimination surveillance in China - Yuan Fang; Yi Zhang (BMC, 2019)
Abstract Background The Global Programme to Eliminate Lymphatic Filariasis (GPELF) was launched in response to the call proposed at the 50th World Health Assembly. The goal of the GPELF is to ensure that all the countries where the disease is endemic would have been transmission-free or would have entered post-intervention mass drug administration (MDA) surveillance by 2020. However, several countries are still not on track to discontinue MDA as planned. Thus, issues remain regarding the achievement of stated goals and how to effectively monitor the disease in the post-control and post-elimination phases. Main text China was once a lymphatic filariasis (LF) endemic country with heavy disease burden. There were three milestones in the LF control phase of China, including: the proposal that the major focus of the control strategy should be on infectious sources; the three regimens of diethylcarbamazine (DEC) administration according to LF endemic extent; and the establishment of the threshold for LF transmission interruption. It has been ten years since China entered the post-elimination stage (declaration of LF elimination in China was in 2007). Two schemes and a diagnostic criterion were issued to guide all levels of disease control and prevention workers that conduct LF surveillance, as well as those caring for chronic filariasis patients. Regular training courses are held to maintain LF control skills in grass-root institutions. The Notifiable Diseases Reporting System, which included LF in 2004, plays an important role in LF post-elimination surveillance. Until now, no resurgence of LF cases has been detected, except for LF residue foci being found in Fuchuan County of the Guangxi Zhuang Autonomous Region. To confirm that transmission is no longer achievable after a decade since the declaration of LF elimination in China, it is expected within the next two years a transmission assessment survey, conducted in previous LF-endemic areas. Conclusions DEC-fortified salt can help accelerate the progress of GPELF before the sprite phase. Sophisticated diagnostic criteria, systematic surveillance regimes, the Direct Network Report system, and regular trainings can effectively prevent the recrudescence of LF during surveillance phases.